Analytical load-moment (P-M) interaction diagrams of GFRP bar reinforced circular geopolymer concrete columns. (December 2021) - Ali, Shehroze; Ahmad, Junaid; Sheikh, M. Neaz; Yu, Tao; Hadi, Muhammad N.S.
Abstract: This study presents an analytical model for the load-moment ( P - M ) interaction diagrams of circular geopolymer concrete (GPC) columns reinforced with glass fiber-reinforced polymer (GFRP) bars and GFRP helices. The analytical P - M interaction diagrams of GPC columns were developed using the layer-by-layer numerical integration method. The analytical predictions of GFRP reinforced GPC columns were then validated against the experimental results on the behaviour of GFRP reinforced GPC columns under different loading conditions. It was found that the developed analytical model predicted the load and moment capacities of GFRP reinforced GPC columns with good accuracy. Further, a parametric study showed that the influence of increasing the compressive strength of GPC was more pronounced on P - M interaction diagrams of GPC columns under concentric and low levels of eccentric axial loadings. Also, the increase in longitudinal and transverse reinforcement ratios resulted in significant improvements in the load and moment capacities of GPC columns reinforced with GFRP bars and GFRP helices.